UPAYA GURU FIQIH DALAM MENINGKATKAN PEMAHAN SISWA PADA MATERI WUDHU DENGAN APLIKASI WHATSAPP KELAS VII DI MTS. YASNAM SAMUSTIDA - Urai Sartika (Tarbiya Islamica, 2016)
The purpose of this study is to find out and get information about: 1) How fiqh teachers' efforts to increase students' understanding of ablution materials using the whatsapp application. 2) What are the supporting and inhibiting factors in improving students' understanding of ablution material. This research uses a qualitative approach and a descriptive type of research. To obtain data related to the focus of the study, researchers conduct interviews, observations and documentation using interview guidelines, observation guidelines using cameras as a data collection tool. The technical data analysis used is a qualitative data analyst. In this study, researchers used three techniques, namely: Data collection analysis, data presentation, drawing conclusions. The data validity check techniques used are trianggulation and member check techniques.